Assessment of a single-phase single-stage grid-connected photovoltaic system - Nurhazwani Anang; Wan Mariam Wan Muda; Muhamad Zalani Daud (Institute of Advanced Engineering and Science, 2023)
A grid-connected photovoltaic (GCPV) system plays an important role in the development of green technology. However, generated photovoltaic (PV) power that is injected into the grid causes instability in the grid system. Previous studies have shown that power quality for a three-phase system is thoroughly being discussed, but not for a single-phase system. Single-phase system also contribute to instability in low-voltage grid networks during high power penetration as majority of the single-phase GCPV nowadays are installed on rooftops. Thus, in this study, the power quality of a single-phase single-stage GCPV system is investigated based on the total harmonic distortion (THD), power factor (PF), and the generated active (P) and reactive (Q) power during different solar irradiance and varying loads conditions. A model of the GCPV system was developed in MATLAB/Simulink, so that certain variables can be varied to observe their effect towards the power quality. The results show that the current and voltage of generated PV power are synchronized and having low current THD which is less than 1% for all cases. PF values are also in the acceptable range in compliance to IEC 61727 standard which is 0.9971, and the generated PQ is in accordance to the connected load.